A judicial review of political questions under Islamic law - O. Sambo, Abdulfatai; Kadouf, Hunud Abia (IIUM Press, 2014)
The contemporary Arab world has witnessed uprisings and turmoil as a result of alleged power-overreaching by political elites. Consequently, people call for democracy with emphasis on constitutionalism, accountability and protection of human rights. Yet, the voice of the judiciary seems not to be heard in championing these values in many Muslim nations despite the clear roles Islam places on the judiciary regarding political matters. This paper therefore analyses the power of judicial review on political questions from the perspective of Islamic jurisprudence. It finds that the power of judicial review and its main institution existed in early Islamic periods after the demise of the Prophet (SAW). The paper concludes that failure to observe judicial review in many contemporary Muslim countries results in the absence of effective checks on the powers of the rulers by the judiciary.